2022
DOI: 10.1049/smc2.12038
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid assessment framework for human‐centred sustainable smart campus: A case study on COVID‐19 impact

Abstract: The continuous development of modern information and communication technologies is driving the smart revolution in the global education system. The outbreak of the COVID-19 pandemic has recently posed unprecedented challenges to educational institutes. The education informatisation technologies are playing a vital role to ensure the continuity and enhance the performance of education during the pandemic, which accelerates the integration of cutting-edge technologies and thus the overall development of the smar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Lastly, this review of research uncovered significant challenges and potential solutions for integrating sustainability into engineering education curricula [37,85,91,120]. The obstacles include the complexities of replacing existing content, resource limitations, a limited understanding of sustainability's social and economic dimensions, and the practical application of sustainability principles in engineering practice [12,72,107].…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, this review of research uncovered significant challenges and potential solutions for integrating sustainability into engineering education curricula [37,85,91,120]. The obstacles include the complexities of replacing existing content, resource limitations, a limited understanding of sustainability's social and economic dimensions, and the practical application of sustainability principles in engineering practice [12,72,107].…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…The concentration of Chinese scholars in this school suggests the significant emphasis Chinese policymakers have placed on leveraging innovative technologies to tackle sustainability challenges [4,78,85,86]. Notably, the network map highlights both the physical isolation of this school as well as limited connections between the Chinese scholars and scholars in the other schools.…”
Section: Intellectual Structure Of Research On Engineering Education ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, introducing edible landscapes in universities can enhance campus viewing and interaction. According to Ribeiro's (2021) research suggests that university sustainable development communication strategies can help enhance students' awareness and importance of sustainable development (Ribeiro et al, 2021) An evaluation index for changes during the lockdown period indicates that the pandemic has significantly increased the sustainability contribution of students, but has had a negative impact on their physical and mental health and safety (Yip et al, 2022). Recent studies have shown that participating in planting activities can effectively alleviate the stress caused by pandemics and help promote mental health.…”
Section: Literature Reviewmentioning
confidence: 99%